"Mouth !" : voix et lieux du pouvoir dans Norma Rae de Martin Ritt (1979) - Corinne Oster (Anglophonia)
Hollywood has never been eager to make movies about the American working class. In the few films that depict social conflict in US society, a few characters, and even fewer women, stand out as the protagonists of a working-class America in which they struggle, often barely surviving, often trying to get out of their condition. Hollywood, indeed, seems to only depict the working class as a setting one aspires to leave, and the pattern frequently found in these films is that of a shift from poverty to a spectacular achievement of the American dream. In many of these films, the way out—or up—for women is more often marriage than a job. Among the few films that stray from that pattern, Norma Rae (Martin Ritt, 1979) thus offers a complex view of a working class woman in the US in the 1970s, inspired by a real factory worker. This article raises a few questions about the film: to what extent does Norma Rae’s social status highlight specific ideological stakes when in situations of conflict? Is she positioned as a stereotypical victim (both of men and of her class), and does she actually gain the power to overcome the conflicts inherent to her status (as a woman and as a member of the working class), hence rewriting the stereotypes that have been established to restrain her? Finally, how is her (new) power presented, and to what extent can it be analyzed as a threat to the patriarchal order?